LOCAL POLITICAL ELITE POWER AND NETWORK GOVERNANCE IN THE IMPLEMENTATION OF POVERTY ALLEVIATION POLICIES: A Case Study of Gresik - Nastain, Muh.; Aminuddin, Muhammad Faishal; Maksum, Ali (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This research discusses the power of local political elites and the application of network governance in the implementation of poverty alleviation policies in Gresik Regency. The main focus of the research is how the dominance of local political elites affects the decision-making process, resource distribution, and policy effectiveness, and how network governance plays a role in overcoming these challenges. The research method used is a qualitative approach with data collection through in-depth interviews, observation, and document analysis. The results show that the dominance of local political elites often prioritises political interests over substantive policy objectives, resulting in unequal distribution of resources and limitations in achieving policy targets. In addition, network governance in Gresik District faces challenges in the form of weak coordination between stakeholders, the limited role of the private sector and civil society organisations, and the lack of active participation of local communities. This research emphasises the need for network governance reform to create more inclusive, transparent, and sustainable poverty alleviation policies. A collaborative approach that involves equal roles between the government, private sector, NGOs, and communities is an important step to improve policy effectiveness. In addition, limiting the dominance of local political elites is necessary to ensure that policies are based on the needs of the community, not political interests alone.gb777